Efektivitas Cockroach Bottle Trap Dengan Atraktan Gula Merah Sebagai Pengendalian Kecoa - Habibie Erlangga Putra (MEJORA Medical Journal Awatara, 2025)
Cockroaches are recognized as mechanical vectors capable of transmitting various pathogens to humans. The continuous application of chemical insecticides often results in resistance and poses risks to human health and the environment. Therefore, safer and environmentally friendly alternatives are needed. This study aimed to evaluate the effectiveness of cockroach bottle traps using fermented palm sugar attractants at three different weights: 15 g, 20 g, and 25 g. A quasi-experimental design with a post-test only control group was employed. The attractant was prepared by melting 100 g of palm sugar, mixing it with 10 g of yeast, and fermenting it for 24 hours. Each treatment was repeated six times across three days of observation, with two test containers used daily. Data were analyzed descriptively and inferentially using the Kruskal-Wallis test. Results showed that the 20 g fermented palm sugar attractant captured the highest number of cockroaches, with an average of 2.5 per replication. Statistical analysis revealed a significance value of 0.028 (p < 0.05), indicating a significant difference among treatment groups. Environmental conditions during the study, including an average temperature of 25.1°C and humidity of 74.3%, were supportive of cockroach activity. In conclusion, fermented palm sugar is an effective natural attractant for cockroach control, and further research should explore alternative attractant forms. This method may serve as a safe, eco-friendly, and low-cost strategy for household cockroach management.